A hundred and one days a Baghdad journal - Seierstad, Åsne 1970- (New York Basic Books, 2005)
Provides a narrative of life in Iraq just before, during, and after the American invasion of March 2003, presenting the opinions and experiences of ordinary Iraqis attempting to carry on some semblance of normal life.
Originally published: London : Virago, 2004.
Keywords: Seierstad, Åsne -- 1970-.; Iraq War, 2003-2011 -- Personal narratives, Norwegian; Iraq War, 2003-2011 -- Journalists -- Biography; Reporters and reporting -- Iraq -- Biography; Iraq -- Social conditions -- 21st century; Iraq -- Social life and customs -- 21st century